2017
DOI: 10.15353/rea.v9i2.1439
|View full text |Cite
|
Sign up to set email alerts
|

Do Exchange Rate Changes have Symmetric or Asymmetric Effects on the Demand for Money in Korea?

Abstract: Previous studies that included the exchange rate in the Korean demand for money assumed that the effects of the exchange rate changes are symmetric and adjustment process is linear. They found no significant effects. In this paper we apply Shin et al.’s (2014) Nonlinear ARDL approach to cointegration and error-correction modeling and test the symmetric versus asymmetric effects of exchange rate changes on the demand for money in Korea. Using quarterly data over the period 1973-2014, the results show that indee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
3
1
Order By: Relevance
“…Inflation, interest rate, and real GDP have no significant effects on money demand in longrun for the three Tunisian considered money aggregates over 2010M01-2019M07 period. These findings contradict the previous findings of (Haider et al, 2017;Mahmood and Alkhateeb, 2018;Bahmani-Oskooee and Baek, 2016;Bahmani-Oskooee and Baek, 2017;Suliman and Dafaalla, 2011).…”
Section: Long-run Estimatescontrasting
confidence: 87%
“…Inflation, interest rate, and real GDP have no significant effects on money demand in longrun for the three Tunisian considered money aggregates over 2010M01-2019M07 period. These findings contradict the previous findings of (Haider et al, 2017;Mahmood and Alkhateeb, 2018;Bahmani-Oskooee and Baek, 2016;Bahmani-Oskooee and Baek, 2017;Suliman and Dafaalla, 2011).…”
Section: Long-run Estimatescontrasting
confidence: 87%
“…Consistent with our findings, Yang [121] and Guzman et al [122] observed the effectiveness of exchange rate stabilization policies in reducing economic volatility. Conversely, Fornaro [123], Bahmani-Oskooee and Baek [124], and Ha et al [125] reported lesser impacts on inflation. Buera and Shin [126], Korinek [127], and Suh [128] highlighted the unintended consequences of increased capital outflows, aligning with our observations of heightened domestic financial pressure under Policy 1.…”
Section: Monetary Balancementioning
confidence: 97%
“…Nevertheless, ambiguity about the sign of the exchange rate in the money demand function indicates the nonlinear behavior of money demand. There is empirical evidence to support that appreciation and depreciation of the domestic currency can have asymmetric effects on the money demand equation (Bahmani‐Oskooee & Baek, 2017; Bahmani‐Oskooee & Bahmani, 2015; Bahmani‐Oskooee & Fariditavana, 2016; Ivanovski & Churchill, 2019). Hsieh and Hsing (2009) provide evidence for a nonlinear behavior in Hungary's money demand function.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In another example, Bahmani-Oskooee and Fariditavana (2016) study nonlinear autoregressive distributed lag (ARDL) to show the symmetric effect of exchange rates on trade balance. Nonlinear ARDL approach in estimating the demand for money has been studied in various counties such as Turkey by , Korea by Bahmani-Oskooee and Baek (2017), and Australia by Ivanovski and Churchill (2019). The method used in these studies is based on a simple linear ARDL for the symmetrical effect and nonlinear ARDL for the asymmetric effect, thereby allowing us to observe the behavior of the demand for money when the exchange rate is increasing or decreasing.…”
Section: Introductionmentioning
confidence: 99%